One technology, two pathways? Strategic Niche Management and the diverging diffusion of concentrated solar power in South Africa and the United States - Mirzania, Pegah; Balta-Ozkan, Nazmiye; Marais, Lochner (Elsevier, 2020)
The transition towards a low carbon energy system requires significant deployment of renewable energy technologies. Concentrated Solar Power (CSP) plants could contribute to a low carbon energy system, with an estimated potential global capacity of over 600 GW by 2030. Despite this potential, however, the CSP industry lags behind other renewable technologies, with only about 4% of its estimated global potential expected to be realised in the next decade. This paper investigates the reasons for this by comparing CSP in the US, where 60% of worldwide capacity is currently located, with South Africa, where its development has been slow despite an abundance of natural solar-energy resources. Using strategic niche management analysis, we identify replicable success factors that could accelerate the uptake of CSP projects in developing countries. The results reveal that the main reason for the successful diffusion and adoption of CSP in the US is consistent policy support, which has made it possible to bridge the gap between research and development and emerge in the market. By contrast, the development of CSP in South Africa has been hindered by several technical and economic problems, including a lack of technological expertise, resources and funding
Keywords: Diffusion; Developing economy; Solar energy; Strategic niche management; Niche formation; Concentrated solar power (CSP)